Media Baru Dan Komunikasi Organisasi (Studi Kasus Pemanfaatan E-Mail, Yahoo! Messenger, Lync, dan Portal Internal dalam Komunikasi Internal PT Datacomm Diangraha): Annisa Risecha Junep - Jurnal COMMED (Prodi Ilmu Komunikasi Universitas Putera Batam, 2016)
PT. Datacomm Diangraha is the company's leading network technology service provider in Indonesia thatprovides solutions and services that are reliable and innovative network nationwide. The purpose of thisstudy was to determine and describe the utilization of e-mail, Yahoo! Messenger, Lync and Internal Portalby ICT in the process of internal communication in PT. Datacomm Diangraha in 2012-2014.Subjects in thisstudy were 3 persons, Mr. Cahyo, HR Manager and Manager ICT PT.Datacomm Diangraha. Data analysistechniques in this research is the data to be obtained from interviews and also from documents of HRD andalso ICT PT. Datacomm Diangraha, After conducting interviews and document study of HR and ICT PT. Theresearch will be conducted by researchers, presentation of data will be done with stories and pictures forfurther clarify the results obtained. Results of the analysis showed that the presence of new media is tofacilitate the process of communication and exchange of information on the company, Improving efficiencyin communication and information, Datacomm be the center of the utilization of new media, as othercompanies began to follow using share point, as well as new media easily accessible and allowing to quicklyobtain feedback